Ricovero avicolo polifunzionale per l'allevamento libero Manuale di autocostruzione - Monti, Massimo (Firenze University Press, 2011)
The book is arranged in the form of a practical, build-it-yourself manual, complete with general technical information and advice for use in the field. The mobile poultry housing has been designed for extensive breeding with animals that have free access to open-air areas during the daytime. With a few simple operations the structure can be adapted for fattening poultry, breeding poultry and chickens; the capacities indicated refer to the European "organic" regulations adopted by Italy. The manual guides the constructor step by step, so that the mobile housing can be built even by those who do not have particular knowledge or skill in wood carpentry; a special section is devoted to safety during work. Finally, there are also a series of recommendations about the positioning of the housing on the land and the completion works necessary to set it in operation.